2015
DOI: 10.1016/j.jconrel.2015.04.034
|View full text |Cite
|
Sign up to set email alerts
|

Molecular weight and concentration of heparin in hyaluronic acid-based matrices modulates growth factor retention kinetics and stem cell fate

Abstract: Growth factors are critical for regulating and inducing various stem cell functions. To study the effects of growth factor delivery kinetics and presentation on stem cell fate, we developed a series of heparin-containing hyaluronic acid (HyA)-based hydrogels with various degrees of growth factor affinity and retention. To characterize this system, we investigated the effect of heparin molecular weight, fractionation, and relative concentration on the loading efficiency and retention kinetics of TGFβ1 as a mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
87
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(92 citation statements)
references
References 53 publications
5
87
0
Order By: Relevance
“…HyA based hydrogels were synthesized using previously reported methods [6, 7, 33]. Briefly, HyA derivative carrying hydrazide groups (HyAADH) was synthesized using previously described methods[3436], and acryloxysuccinimide (700 mg) was subsequently reacted to the HAADH solution (300mg, 100 mL DI water) to generate acrylate groups on the HyA (AcHyA)[3638].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…HyA based hydrogels were synthesized using previously reported methods [6, 7, 33]. Briefly, HyA derivative carrying hydrazide groups (HyAADH) was synthesized using previously described methods[3436], and acryloxysuccinimide (700 mg) was subsequently reacted to the HAADH solution (300mg, 100 mL DI water) to generate acrylate groups on the HyA (AcHyA)[3638].…”
Section: Methodsmentioning
confidence: 99%
“…In view of these issues, we have proposed that Matrix-Assisted Cell Transplantation (MACT) might be used to promote pro-survival autocrine/paracrine signaling and to enhance engraftment [6, 7]. The design of synthetic matrices for cell transplantation includes biochemical and mechanical factors that promotes cell adhesion, proliferation, and differentiation, and stimulates engraftment of donor cells and tissue regeneration.…”
Section: 0 Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…5,42 Therefore, a number of biomaterials have been decorated with heparin or heparin sulfate-mimetic molecules, sequestering the heparin-binding ability of GFs to improve their delivery. For example, Jha et al 43 developed a series of heparin-functionalized hyaluronic acid-based hydrogels and investigated the effect of heparin molecular weight (MW) and its relative concentration on the loading efficiency and retention behavior of TGFβ1. The results demonstrated that high MW heparin facilitated TGFβ1 loading and retention and exhibited the slowest release kinetics, which was primarily due to its higher affinity for TGFβ1 compared to low MW heparin.…”
Section: Ecm-inspired Gf Delivery Systemsmentioning
confidence: 99%